Malaysian scholarly e-journals: focus on EJUM, a journal management system - Zainab, A.N.; Edzan, N.N. (2000)
Presents an overview of the various Malaysian scholarly electronic journals available on the Internet and describes the issues involved in setting up a journal hosting system which currently publishes the Malaysian Journal of Library & Information Science (MJLIS) and Malaysian Journal of Computer Science (MJCS). Both journals are accessible via the Internet in 1999 with its print equivalent still being published and distributed.